ANALISIS EVALUASI SISTEM PENGENDALIAN INTERNAL DALAM SIKLUS PENERIMAAN KAS PADA PT. â€œXâ€ SURABAYA - Setya Kusprianti, Sri Alam (Jurnal Akuntansi AKUNESA, 2014)
This research was done to know how effective the operation sistem whichwas already applied at PT.?X?. It used the descriptive qualitativeresearch method. This observation data is about internal operationsistem activity that is applied at PT.?X?. Accounting information sistemis a component which shall be applied in an industry. It has a closerelationship with internal operation sistem. Accounting informationsistem that was used by PT.?X? is cash acceptance cycle. It is known thatcash was an activa which has a liquid characteristic, so then it is easierto do some frauds. Internal operation sistem was used to minimalize it.Based on data analysis, internal operation sistem has already beenapplied effectively at PT.?X?. It is proved by a good proper internaloperation elements that were applied there and separation of tasks thathas been done to minimalize frauds.Keyword: internal operation sistem, cash acceptance cycle